Mafic macrocrysts of ultrabasic alkaline dikes from the Mantiqueira Range, SE, Brazil: tracers of a complex plumbing system - Silva,Júlio César Lopes da (2020)
Abstract Macrocryst assemblages of porphyritic alkaline dikes in the Mantiqueira range (SE Brazil) are mainly composed of clinopyroxene and olivine with different origins. Based on petrographic features, mineral chemistry, and equilibrium relationships with the host liquid, those macrocrysts are classified as xenocrysts, antecrysts, and phenocrysts. Described xenocrysts are mantle olivine, Cr-diopside cores compatible with garnet-bearing mantle facies, green-core clinopyroxene cores compatible with lower crust, and enstatite cores mantled by clinopyroxene, all reported for the first time in this region. Two contrasting types of clinopyroxene antecrysts prevail among the macrocryst cores (both occurring in the same samples and presenting corrosion and sieve textures): primitive colorless diopside and more evolved green-core clinopyroxenes. In the studied rocks, green clinopyroxene zones mantling colorless diopside cores (and vice-versa) are also found. Diopside- and green-cores antecrysts have similar compositions to those from mafic and felsic alkaline melts, respectively. Phenocrysts are mainly related to Ti-augite overgrowths, mantling all other types. Mixing-model curves between mafic and felsic alkaline equilibrium liquids calculated from clinopyroxene antecrysts indicate a hybrid origin for the host matrix. The macrocryst populations of the studied dikes are indicative of a complex plumbing system, recording several processes of an open-system magmatic evolution.